1845 Iowa Acts 119 - (:unkn) unknown (My University, 1845)
An Act to Incorporate and Establish the City of Dubuque, chap 123, § 12: The city of Dubuque shall have the authority to regulate the storage of gun powder.
Keywords: GUNPOWDER - STORAGE